Application of a Novel Radioimmunoassay to Identify Baculovirus Structural Proteins That Share Interspecies Antigenic Determinants - Smith, Gale E. (1981)
Immunological comparisons were made of baculovirus structural proteins by using a modification of the radioimmunological techniques described by Renart et al. (Proc. Natl. Acad. Sci. U.S.A. 76: 3116-3120, 1979) and Towbin et al. (Proc. Natl. Acad. Sci. U.S.A. 76: 4350-4354, 1979). Viral proteins were electrophoresed in polyacrylamide gels, transferred to nitrocellulose, and incubated with viral antisera, and the antibodies were detected with (125)I-labeled Staphylococcus aureus protein A. Antisera were prepared to purified and intact virions from five baculoviruses: Autographa californica, Porthetria dispar, Trichoplusia ni, and Heliothis zea nuclear polyhedrosis viruses (NPVs) and T. ni granulosis virus (GV). These antisera were tested against the virion structural polypeptides of 17 different species of baculoviruses. Specific multiple-nucleocapsid NPV (MNPV), single-nucleocapsid NPV (SNPV), and GV virion polypeptides were shown to have similar antigenic determinants and thus be immunologically related. The molecular weights of the virion polypeptides with cross-reacting antigenic determinants were identified. Antisera prepared to purified A. californica and H. zea MNPV polyhedrin (the occlusion body protein from NPVs) recognized antigenic determinants on all the polyhedrins and granulins (occlusion body protein from GVs) that were tested. No immunological relationship was detected between A. californica MNPV polyhedrin and any of the A. californica MNPV virion structural polypeptides present on either the virus isolated from occlusion bodies or A. californica MNPV extracellular virus from infected-cell cultures.